Marker Based Standardization of Herbal Sunscreen Formulation by Using Validated High-Performance Thin Layer Chromatography Method: Pharmaceutical Science-Pharmacognosy for Efficient Natural Therapy - Sutar Manisha P; Chaudhari Sanjay R (International Journal of Life Science and Pharma Research, 2022)
Plant based products are worldwide used and trusted for the care and cure of the health. Herbal sunscreen formulations are gaining popularity for their effectiveness and are devoid of side effects. The present investigation is an effort made to develop herbal sunscreen cream containing methanolic extracts of different plants and its standardization for the presence of bioactive compounds. The leaves of Cymbopogon citratus (Stapf), fruit peel of Punica granatum (Linn), flowers of Butea monosperma (Lam.) and leaves of Neolamarckia cadamba (Roxb.) were selected for the preparation of sunscreen cream. The standardization of herbal formulations is very important to determine its quality based on the concentration of their active phytoconstituents. The herbal cream F-5 (2 % w/w) imparted its sun-protective and antioxidant property. It shows free radicals scavenging activity due the presence of flavonoids and phenolic compounds. High performance thin layer chromatography method is used to determine the quality and quantity of the sun protective phytoconstituents present in the product. The method was validated according to ICH guidelines for the estimation butrin (BT), isobutrin (IBT), quercetin (QC), apigenin (API), chlorogenic acid (CA) and gallic acid (GA) using the optimized solvent systems. The estimation of bioactive markers was carried out on silica gel precoated thin layer chromatography plates with 60F254 as the stationary phase and Camag TC scanner III for densitometric scanning. The average Rf values for the markers were found to be 0.46 for BT, 0.57 for IBT, 0.50 for QC, 0.57 for API, 0.66 for CA and 0.42 for GA. The developed HPTLC method was linear with correlation coefficient 0.999 for BT, 0.998 for IBT, QC, API and 0.9966 for CA and 0.9989 for GA. Limit of detection (LOD) and limit of quantification (LOQ) were recorded. The developed analytical method for quantitative determination of phytoconstituents was found efficient, simple, accurate, and validated.